2019
DOI: 10.1063/1.5109021
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of magnetic nanoparticle in thermal conductivity of flake-shaped iron particles based magnetorheological (MR) fluid

Abstract: Magnetorheological (MR) fluids were prepared in transformer oil as well as transformer oil based magnetic fluid having 2 wt. % of Fe3O4 particles. The thermal conductivity enhancement (w.r.t. carrier) in the case of transformer oil based MR fluid under a field was found to vary from 219%, 304%, and 356%, respectively, from 15 vol. %, 20 vol. %, and 25 vol. % of iron concentration. These values are much higher than that obtained for spherical-shaped iron particles based MR fluids. This is further enhanced by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Thus, it was found that whenever the magnetic field strength and the dispersed volume fraction are greater and the size of the particles is smaller, the thermal conductivity of the MRF is further increased. Pisuwala [55] presented the thermal properties of MRFs made of transformer oil and 2 wt.% of Fe 3 O 4 particles. Firstly, it was shown that the thermal conductivity is enhanced by 219%, 304%, and 356% by changing the iron concentration from 15 vol.%, 20 vol.%, and 25 vol.%, respectively.…”
Section: Temperature Effect and Thermal Conductivitymentioning
confidence: 99%
“…Thus, it was found that whenever the magnetic field strength and the dispersed volume fraction are greater and the size of the particles is smaller, the thermal conductivity of the MRF is further increased. Pisuwala [55] presented the thermal properties of MRFs made of transformer oil and 2 wt.% of Fe 3 O 4 particles. Firstly, it was shown that the thermal conductivity is enhanced by 219%, 304%, and 356% by changing the iron concentration from 15 vol.%, 20 vol.%, and 25 vol.%, respectively.…”
Section: Temperature Effect and Thermal Conductivitymentioning
confidence: 99%
“…Nanoparticles are often applied as additives to insulation liquid medium, which can greatly improve the insulation performance of the insulation liquid. However, due to the incompatibility between nanoparticles and natural ester insulation oil, agglomeration would occur, which could affect the stability of insulation oil, lead to insulation faults, and threaten the normal operation of the power grid. , In order to make nanoparticles stably disperse in insulation liquid for a long time, surface modification technology is commonly applied to improve the compatibility between nanoparticles and insulation oil. , Zhou prepared natural ester insulation oil doped with oleic-acid-modified Fe 3 O 4 nanoparticles . The functional groups and thermal stability of surface-modified Fe 3 O 4 nanoparticles were studied by a differential thermal analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in the dielectric materials field, the usage of nanomaterial modification technology has been the research hotspot [1], [2], and it can be used to improve the electricity [3], [4], heat conduction [5], [6] and aging [7], [8] of insulation oil. Yuxiang Zhong and his team found that TiO 2 nanoparticles not only enhance the AC breakdown voltage of ester-based nanofluid, but also improve the partial discharge performance of ester-based nanofluids compared to natural esters [9].…”
Section: Introductionmentioning
confidence: 99%